Motivasi dan Efikasi Diri (Self Efficacy) dalam Manajemen Perawatan Diri Pada Pasien Diabetes Mellitus Tipe 2 - Muhammad Basri; Sitti Rahmatiah; Dwi Sastra Andayani; Baharuddin K; Ramlah Dilla (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: High motivation and self-efficacy in the implementation of treatment in DM patients will result in increased self-care. Therefore, increasing the self-confidence and motivation of patients will improve their self-care management. Objective: To identify the relationship between motivation and self-efficacy in self-care management in patients with type 2 diabetes mellitus. Method: Research with a literature study approach. Data were collected using a literature review of several articles published in Google Scholar, Proquest and PubMed published in 2015-2021. Results: Based on 10 journal search results, the majority of journals discussed the relationship between education level, gender, motivation, and self-efficacy in performing good self-care management in type 2 diabetes mellitus patients. Conclusion: The relationship between motivation and self-efficacy of type 2 diabetes mellitus patients in management self-care is closely related. Motivation is a very important factor for self-care management as well as the higher the self-efficacy value of a DM patient, the higher the patient's belief in self-care related to their disease